008 Risk assessment of patients presenting to the ED with chest pain and equivocal cardiac troponin T (cTnT) levels: the lost tribe?. (14th September 2011) - Cook, C; Krom, A; Sood, T
Abstract : Objectives and Backgrounds: New high-sensitivity cTnT assays are being used to determine myocardial necrosis. These tests include an equivocal range for myocardial necrosis (0.014–0.030 μg/l), data on both clinical risk and outcomes for this group are limited. There is no explicit national guidance on the management of patients presenting with chest pain and equivocal cTnT values. Objectives: (1) Individually risk asses patients presenting to the ED with chest pain and equivocal cTnT values [0.014 to <0.03 μg/l] for future adverse cardiovascular events using the Global Registry of Acute Cardiac Events [GRACE] risk scoring system. (2) Record the referral/discharge pathways of these patients. Methods: Patients presenting to the ED with cTnTs in the equivocal range over a 1-month period were identified. Future risk of adverse cardiovascular events was retrospectively calculated using the GRACE risk scoring system. Results: 40 patients with cardiac type chest pain, adequate documentation and equivocal cTnT levels were identified. 49% of these patients were assessed as "high risk", 36% "medium risk" and 15% "low risk" when retrospectively GRACE scored. Of the "high risk" patients, 58% were discharged home without any documentation of specialist involvement, in-patient [IP] investigation or follow-up. 72% of these patients may have been suitable for IP angiogram ± intervention within 96 h of admission, but just 15% of these patients received this. Conclusions: Patients with cTnT concentrations in the equivocal range present a diagnostic dilemma for the ED clinician. They appear at increased risk of ACS when applying clinical risk stratification using a GRACE score. This increase in risk appears poorly appreciated, leading to opportunities for intervention being missed.